Topologically designed electrospun peculiar three-sided walnut shaped microfiber array membrane exhibits superior poly-function. (1st March 2023) - Hu, Yaolin; Qi, Haina; Shao, Hong; Yang, Liu; Ma, Qianli; Sheng, Yuqi; Xie, Yunrui; Yu, Wensheng; Li, Dan; Dong, Xiangting
Abstract: The designed microscopic structure partitions for poly-functional polymer composites are significant ways to accelerate the development of materials science. Herein, a novel flexible one-dimensional three-sided walnut shaped (abbreviated as TWS) microfiber is firstly designed and built via electrospinning by using an especial tri-axis spinneret. As a case research of expanding applications, the unique structured [Tb(SSA)3 (TPPO)2 /polymethylmethacrylate (PMMA)]//[polyaniline (PANI)/PMMA]//[CoFe2 O4 /PMMA] (marked as [TST/P]//[P/P]//[C/P]) photoluminescent-conductive-magnetic poly-functional TWS microfiber array membrane (abbreviated as PTMAM) are constructed by directional arrangement of the TWS microfibers. Through the elaborate topology design, the TWS microfiber realizes the division of three independent micro functional regions. By restricting the photoluminescent, conductive and magnetic media in their respective domains, the harmful interactions among the three functions are efficaciously avoided, thus enabling outstanding photoluminescent-conductive-magnetic poly-functions. By adjusting the concentrations of Tb(SSA)3 (TPPO)2, PANI and CoFe2 O4 NPs, PTMAM exhibits adjustable photoluminescence, aeolotropic conduction and magnetism. The photoluminescence can be used to detect whether PTMAM normally operates or abnormally operates in darkness. The formation mechanisms of TWS microfibers and array membrane are expounded. In addition, this unique TWS microfiber realizes the pairwise contact of each construction block, forming a unique heterostructure, which is expected to play a significant role in catalysis, energy storage and other fields. Graphical abstract: Image 1 Highlights: Topologically designed novel three-sided walnut shaped (TWS) microfiber is advanced. TSW microfiber and array are designed and prepared by a tri-axis electrospinning. Partition of three independent aeras in TWS microfiber is microscopically realized. Green fluorescence endows the array membrane with unique visualization feature. Conductive anisotropy, magnetism and luminescence are highly integrated into array.